2017
DOI: 10.1002/jca.21551
|View full text |Cite
|
Sign up to set email alerts
|

Impact of plerixafor (mozobil) on hospital efficiency: A single center experience

Abstract: Plerixafor (Mozobil) in combination with granulocyte colony-stimulating factor (G-CSF) has shown to increase mobilization of peripheral blood stem cells (PBSC) as compared to G-CSF alone in patients undergoing autologous stem cell transplantation (ASCT). However, up to 25% of patients treated with G-CSF alone still fail mobilization. Adding plerixafor to poor mobilizers allows to rescue these patients from mobilization failure and to reduce the number of apheresis sessions. The goal of this retrospective study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…Previous studies within our department reported that the use of plerixafor to aid peripheral blood stem cell mobilization in patients undergoing autologous stem cell transplantation reduced the mean number of apheresis time‐slots lost per patient from 1.39 to 0.89 and increased the predictability of available time‐slots . This allowed the department to dedicate resources for ECP procedures.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies within our department reported that the use of plerixafor to aid peripheral blood stem cell mobilization in patients undergoing autologous stem cell transplantation reduced the mean number of apheresis time‐slots lost per patient from 1.39 to 0.89 and increased the predictability of available time‐slots . This allowed the department to dedicate resources for ECP procedures.…”
Section: Discussionmentioning
confidence: 94%
“…Studies adopting a wider perspective which captures additional costs incurred to the hospital due to mobilization failure (e.g. delay in treatment, disruption of patient flow, inability to proceed to transplantation) have shown that plerixafor improves the use of apheresis capacities and may even be cost-saving [18,22,27]. Here, a narrow perspective was selected on purpose to decrease the institution-specific variations and to increase the generalizability of our results.…”
Section: Discussionmentioning
confidence: 99%
“…Plerixafor may also rescue patients from mobilization failure in case of poor mobilization in response to G-CSF only [15][16][17]. Several cost-effectiveness studies have shown that plerixafor, when given to poor mobilizers, decreased mobilization failure rates at an acceptable increase in costs for patients with MM and NHL [13,[18][19][20]. A direct comparison between studies is hampered because of differences in the ASCT procedure and local guidelines, health care provision, and reimbursement.…”
Section: Introductionmentioning
confidence: 99%
“…24 While 25% of patients treated with G-CSF alone still failed mobilization, upon the addition of plerixafor, the failure rate would drop to 4%. 25…”
Section: Mobilizationmentioning
confidence: 99%